2013
DOI: 10.3174/ajnr.a3459
|View full text |Cite
|
Sign up to set email alerts
|

Can MRI Replace CT in Evaluating Semicircular Canal Dehiscence?

Abstract: BACKGROUND AND PURPOSE:Patients with symptoms of semicircular canal dehiscence often undergo both CT and MR imaging. We assessed whether FIESTA can replace temporal bone CT in evaluating patients for SC dehiscence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 20 publications
3
49
0
4
Order By: Relevance
“…The positive predictive value for the use of MRI was 93.4% and the negative predictive value 83.7% in our study group. This positive predictive value was close to that found in similar studies in the literature [8,10] ; however, the negative predictive value of MRI was lower (33.3%) in a study published by Browaeys et al [10].…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…The positive predictive value for the use of MRI was 93.4% and the negative predictive value 83.7% in our study group. This positive predictive value was close to that found in similar studies in the literature [8,10] ; however, the negative predictive value of MRI was lower (33.3%) in a study published by Browaeys et al [10].…”
Section: Discussionsupporting
confidence: 48%
“…To the best of our knowledge, the first similar study on this subject was reported by Krombach et al [11] in 2004, who found that MRI had a sensitivity level of 96% and a specificity level of 98%. Subsequent studies showed similarly high sensitivity and specificity levels [8,10] .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is an essential imaging technique as well to confirm the diagnosis of the dehiscence. Recently Browaeys et al proposed MRI as screening tool for dehiscence exclusion (sensitivity of 100 % and specificity of 99.1 %) [16]. Although MRI can give a false positive result for the inner ear dehiscence, in the present cases the MRI findings were correlated well with the clinical data.…”
Section: Discussionsupporting
confidence: 72%
“…Según Krombach y col 48 la RM tiene una sensibilidad del 96% y una especificidad del 98% y según Browayes y col 49 obtuvieron una sensibilidad y un valor predictivo negativo del 100%, una especificidad del 99,1% y un valor predictivo positivo del 33,3%. Inal y col 50 concluyen que se realice RM para el diagnóstico de una dehiscencia y solo en caso de duda se debe realizar un examen de TC.…”
Section: Estudios De Imagenunclassified